PENGARUH KOMPETENSI, MOTIVASI DAN DISIPLIN TERHADAP KINERJA PENDIDIK DENGAN KONTRAK KERJA DI SMK NEGERI 1 SUMBERASIH KABUPATEN PROBOLINGGO - jurnalmap map; Agus Purnomo; Nugroho Mardi Wibowo (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
One of the significant things which is very important in providing educational services is the teaching staff (teacher) which in this study emphasizes to the work contract teaching staff so that their performance is increasing.The purpose of this study is to describe, analyze significantly and simultaneously, influence directly competence, motivation and discipline on performance at SMK Negeri 1 Sumberasih, Probolinggo. In order to analyze the causal relationships between variables and test hypotheses, the analysis used is multiple regression analysis.Based on the results of descriptive analyzes known that competency, motivation, discipline and performance have good values: and based on multiple linear regression analysis known that competence is not positive effect and not significant to performance; motivation have positive and significant influence for performance; discipline have positive and significant influence toward performance and competence, motivation and discipline are influence simultaneously to the performance.